The pandemic and isolation: an analysis of its first consequences on the vulnerable population. A case study (Revista de Investigaciones Universidad del Quindío, 2022)
The pandemic has unleashed a global crisis. In this work, an analysis is carried out on the first consequences of pandemic and isolation on the vulnerable population, under the hypothesis that they could form a new group of excluded when the “new normal” arrives. A methodological strategy of combining quantitative and qualitative analysis is used on three vulnerable neighbourhoods in Bahía Blanca. It is concluded that this population is severely affected by the pandemic and crisis, favouring the outcome in new exclusion trajectories.
Keywords: social isolation; pandemic; vulnerability; informality; Bahía Blanca